Kunci Identifikasi Ordo Thysanoptera pada Tanaman Pangan dan Hortikultura - Dewi Sartiami (Jurnal Ilmu Pertanian Indonesia, 2008)
Thysanoptera is a minute insect. It acts as pest, plant virus vector and predator. In this research, the thrips on crop and horticulture have been collected at Bogor and its surrounding. The result of this research was found 16 specieses which is consist of two suborders, that are Tubulifera and Terebrantia. On this two subordos, there are three families, Phalaeothripide, Aeolothripidae and Thripidae. This research also present an identification key of Thysanoptera which is built from these 16 specieses. The images of thrips characters were captured with digital camera to complete the explanation of identification key.Keywords: horticulture, identification, plant crop, thysanoptera